Memahami Pola Belajar Generasi Z Sebagai Dasar Pengembangan Media Pembelajaran IPS di IAIN Metro - Wellfarina Hamer (MENDIDIK: Jurnal Kajian Pendidikan dan Pengajaran, 2022)
This study aims to find out more about the characteristics and changes in the learning style of Z Generation, namely IAIN Metro IPS students as the basis for developing social studies learning media. This research is a type of qualitative research with a case study approach. The data collection techniques used are interviews (interviews), observation and documentation then to ensure the validity of the data using technical triangulation and source triangulation followed by data analysis with the research flow, namely identifying problems, determining research design, determining the role of research, determining data collection procedures, recording data, analysis and verification of data as well as narrating the research results obtained. The results of the study show that the learning patterns of Generation Z, in this case the students of Tadris IPS IAIN Metro, are: 1. Students really need a fast device or technology to get the source of information they need 2. Students really like learning with more hands-on practice or learning styles. Doing. 3. Characteristics of students who are multi-tasking where they can do several things at one time. 4. Students need lecturers who position themselves as sources of information and friends to discuss. 5. Students need clear learning objectives and quick feedback before the learning process takes place. 6. Students need interesting learning media based on audio, audio visual and electronic books that are easily accessible for study references.